Simultaneous Observations of a Polar Cap Sporadic‐E Layer by Twin Incoherent Scatter Radars at Resolute. Issue 6 (29th May 2022) - Wang, Yong; Themens, David R.; Wang, Cheng; Ma, Yu‐Zhang; Reimer, Ashton; Varney, Roger; Gilies, Robert; Xing, Zan‐Yang; Zhang, Qing‐He; Jayachandran, P. T.
Abstract: At high latitudes, the Sporadic‐E layer (Es layer) is a common phenomenon but is still poorly understood due to sparse measurements and the difficulty of conventional mechanisms to operate. In this study, an interesting case of polar cap Es layer is first studied by using the twin incoherent scatter radars (northward‐looking face of Resolute Incoherent‐Scatter Radar and Resolute Incoherent‐Scatter Radar‐Canada), a Canadian Advanced Digital Ionosonde, and a Magnetometer, all at Resolute, Canada. From several electron density profiles of the twin radars, the horizontal scale of the polar cap Es layer is found to be greater than 350 km. Moreover, the polar cap Es layer is determined to be drifting from the bottom F region (>150 km) to the lower E region. Furthermore, a unique appearance of double polar cap Es layers is observed. As a result, these peculiar signatures inspire a newly proposed process that involves the combination of localized electric fields and gravity waves. Plain Language Summary: The Sporadic‐E layer (Es layer) is a globally common phenomenon, which is comprehensively and unceasingly studied in decades by using the observation measurements and numerical simulations. The remarkable agreements on the characteristics and generation mechanisms of Es layer at middle latitudes have then been almost achieved. However, over the polar region, it is still poorly understood due to sparse measurements and the difficulty of conventional mechanisms to operate. In this study, an interesting case of polar cap Es layer are first reported by using the twin radars of northward‐looking face of Resolute Incoherent‐Scatter Radar and Resolute Incoherent‐Scatter Radar‐Canada, Canadian Advanced Digital Ionosonde, and Magnetometer simultaneously. Through comprehensively studies, the understanding of polar cap Es layer is clearly extended, not only on the characteristics but also on the mechanism processes. The polar cap Es layer is horizontally greater than 350 km; a new process on the generation mechanism is provoked including the functions of particle precipitation and gravity wave. As a consequence, we present a peculiar evidence for the first time to greatly enrich our knowledge on the polar cap Es layer, showing us a new insight on it. Key Points: An amazing example of polar cap Es layer is first presented by the twin radars of northward‐looking face of Resolute Incoherent‐Scatter Radar and Resolute Incoherent‐Scatter Radar‐Canada at Resolute, Canada simultaneously The morphology of the polar cap Es layer is comprehensively furthered, interpreting the horizontal scale size (>350 km) and double layers To reasonably explain this phenomenon, a new process is hypothesized, consisting of localized electric field and gravity wave